2021
DOI: 10.1007/s42452-021-04235-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of ionic liquid microemulsion for transdermal delivery of a chemotherapeutic agent

Abstract: Nowadays skin cancers have become a major area of concern because of the continuous exposure to sun rays (UV rays). Hence, the present work focused on the synthesis of an innovative 5-Fluorouracil (5-FU) microemulsion as a topical delivery system mainly used to treat various forms of skin cancer. The topical administration of most of the active compounds is impaired by limited skin permeability due to the presence of skin barriers. In this sequence, the microemulsion represents a cost-effective and convenient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The prepared microemulsion gel formulation exhibited enhanced permeation, increased flux, and drug infusion into goat and human cadaver skin with lower irritation than that for free 5-FU. Hence, this microemulsion could be employed as a potential drug carrier system in various forms of skin cancer for future applications . El-Gogary et al encapsulated oleuropein within a microemulsion formulation to increase oleuropein’s permeation efficiency for treating skin disorders like psoriasis.…”
Section: Nanocarriers For Topical Drug Deliverymentioning
confidence: 99%
“…The prepared microemulsion gel formulation exhibited enhanced permeation, increased flux, and drug infusion into goat and human cadaver skin with lower irritation than that for free 5-FU. Hence, this microemulsion could be employed as a potential drug carrier system in various forms of skin cancer for future applications . El-Gogary et al encapsulated oleuropein within a microemulsion formulation to increase oleuropein’s permeation efficiency for treating skin disorders like psoriasis.…”
Section: Nanocarriers For Topical Drug Deliverymentioning
confidence: 99%
“…Egorova et al [65] conducted a study to evaluate the potential influence of common imidazolium ILs on the activity of well-known anticancer agents, mitoxantrone and doxorubicin, both of which are recognized for their cytotoxic effects and intrinsic ionic properties. The cytotoxicity was assessed using CaCo-2 cells, a human colorectal adenocarcinoma cell line, which served as the biological model to evaluate Additionally, another study reported that IL-in-oil microemulsions (IL/O MEs) improved the solubility and transdermal delivery of the sparingly soluble drug, 5-fluorouracil (5-FU) [66]. 5-FU microemulsions (5 %) were formulated in three batches with different ratio, denoted as ME1, ME2, and ME3.…”
Section: Ils In Cancer Treatmentmentioning
confidence: 99%
“…Additionally, another study reported that IL‐in‐oil microemulsions (IL/O MEs) improved the solubility and transdermal delivery of the sparingly soluble drug, 5‐fluorouracil (5‐FU) 66. 5‐FU microemulsions (5 %) were formulated in three batches with different ratio, denoted as ME1, ME2, and ME3.…”
Section: Ils In Cancer Treatmentmentioning
confidence: 99%
“…Thus, in this case they are being incorporated into microemulsion for improving the permeability of the drug. So that it can produce its anti-cancer activity [68]. 5-fluorouracil is being studied by many of the researchers by incorporating them into a microemulsion for rehabilitation of skin cancer [69].…”
Section: Topical Routementioning
confidence: 99%